Efektivitas Metode Manipulatif dengan Media Konvensional dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas III SDN 060937 Medan - Putra Fahlevi; Amin, Teguh Satria; Ovami, Debbi Chyntia; Hutasoit, Putri Romauli (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to test the effectiveness of manipulative methods in improving mathematics learning outcomes of third grade students at SDN 060937 Medan. This type of research is classroom action research, with 20 students in class III as research subjects. To obtain data, the author conducted a learning outcome test before (pretest) and after the learning process (posttest). Data analysis used in this study is descriptive qualitative. The results of the study in cycle I showed that 13 students did not achieve the Minimum Completion Criteria (KKM) set, which was 75, with an average score of 70. Meanwhile, the results of the study in cycle II showed an increase, where 17 out of 20 students achieved completion, with an average overall score of 82.7. These findings indicate that manipulative methods are an effective strategy in improving mathematics learning outcomes in class III.